2018
DOI: 10.1093/schbul/sby179
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Bodily Maps of Emotions in Schizophrenia

Abstract: Objective Embodied emotions arise from interoceptive and somatosensory processes, and are essential to the development of a stable sense of self. Emotional embodiment is therefore inherently interwoven with our sense of bodily self-awareness, and allows us to navigate complex social situations. Given that the core feature of schizophrenia (SZ) is characterized by the presence of bodily self-disturbances and social-emotional deficits, we hypothesized that embodiment of emotion would be disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
78
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 34 publications
7
78
1
Order By: Relevance
“…Experiments with the emBODY tool in large samples of healthy participants revealed that different emotions are consistently associated with different bodymaps [9,10]. These body-maps of emotions are consistent across different cultures [9], developed between age 6 and 17 to become spatially specific [11], and they appear to be altered in clinical conditions [12].…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Experiments with the emBODY tool in large samples of healthy participants revealed that different emotions are consistently associated with different bodymaps [9,10]. These body-maps of emotions are consistent across different cultures [9], developed between age 6 and 17 to become spatially specific [11], and they appear to be altered in clinical conditions [12].…”
mentioning
confidence: 92%
“…Second, we analyzed the number of colored pixels corresponding to activation and deactivation for each emotional word per participant [12] (Fig. 1c).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In schizophrenia, this basic sense of the bodily self is disrupted (Bleuler, 1911;Sass and Parnas 2003). Narratives of aberrant self experiences (e.g., Kean 2009;Saks, 2007) are supported by contemporary empirical evidence documenting anomalous body ownership, agency, and emotional embodiment in this population (Hur et al, 2014;Raballo et al, 2021;Thakkar et al, 2011;Torregrossa et al, 2019). Importantly, such anomalous self-experiences predate schizophrenia onset (Nelson et al, 2012) and may lead to social impairments and disconnection (Michael and Park, 2016).…”
Section: Introductionmentioning
confidence: 99%